Awareness and Perception of Gold Ornament Buyers in Bangalore- A Mixed Method Approach - Eshwar, Lakshmi; Selvalakshmi, G. (Indian Journal of Information Sources and Services, 2024)
Purpose: This study aims to examine the level of Awareness among gold ornament buyers in Bangalore and assess its influence on their purchase intention towards gold ornaments. This study investigates the perception of gold ornaments among buyers in Bangalore. The study also understands the behavior of gold buyers regarding the online purchase of gold ornaments and the role of digital marketing on the purchase intention of gold buyers. Methods: The current study uses a mixed research approach based on primary data from gold ornament buyers and sellers. For quantitative analysis, a sample size of 109 respondents was calculated using the Kregcie-Morgan table with a 10% margin of error. Convenience sampling was employed for the sampling process. Nine questions were posed regarding the Awareness of gold ornaments; six about the online purchase of gold ornaments; and three about the intention to purchase gold ornaments. The validity and reliability of the questionnaire were assessed using the Gaskins master validity table. The data was gathered using Google Forms and the survey methodology. This study used SPSS and confirmatory factor analysis using AMOS software for data interpretation. The data obtained through qualitative interviews with gold ornament sellers was transcribed and analyzed using the Nvivo 14 software. Findings: The study's results reveal that age, qualification, and income significantly affect the Awareness of gold ornament features among the buyers of gold ornaments. Awareness of gold ornament features significantly affects customers' purchase intention. The results revealed that e-commerce websites' reliability, trust, and security were the most important considerations when purchasing Gold online. The use of online applications has also enhanced customers' understanding of price comparison, design, and information on quality checks. The qualitative analysis revealed two major points: the advantages and disadvantages of gold ornament purchases. Implications: The study's implications show that a marketing approach tailored to a specific target market’s demographic characteristic may lead to increased sales and customer satisfaction. By better understanding the preferences and needs of the defined segments, gold ornament retailers can genuinely reflect the preferences of the customers in their strategies and maintain their demand. Originality: The study's novelty is based on a comprehensive analysis of customer segmentation strategies in the gold ornaments field. This strategy has the potential to benefit multiple retailers by obtaining a competitive advantage. At the same time, this study highlights the need to remain flexible, always improve, and adjust marketing efforts based on customer preferences and industry shifts.